GAMBARAN TINGKAT PENGETAHUAN REMAJA PUTRI TENTANG KANKER PAYUDARA DAN PERILAKU PEMERIKSAAN SADARI - Yanita Trisetiyaningsih; Fitriani (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: One way that can be done to reduce the incidence of breast cancer is by breast self-examination (BSE). The lack of awareness of Indonesian women in conducting early detection of breast cancer, even many Indonesian women do not yet know the ways to detect breast cancer early causing a large enough incidence of breast cancer. Junita (2011) states that knowledge, attitudes are still lacking due to lack of information and lack of awareness about examinations Objective: Knowing the description about the level of knowledge of adolesscent women about breast cancer and the behavior of breast self-examination. Methods: This research is description research. The method used in this study is a survey, through interviews using a questionnaire with a cross-sectional approach. Population in this research is second class daughter (class IX) with number of 8 class in SMA Muhammadiyah 4 Kotagede Yogyakarta as many as 78 respondents. Result: The level of knowledge about breast cancer with enough category as many as 55 student (70,5%), good knowledge 9 student (11,5%), and less of knowledge 14 female students (17,9%). Behavior BSE with good category as much 17 (21,8%), enough 47 (60,3%) and less 14 (17,9%). Conclusion: Based on the results of research on the level of knowledge about breast cancer shows that most of the knowledge of female students have enough knowledge as much as 55 students (70.5%).Based on the results of research table about the frequency distribution behavior of breast self-examination shows that the greatest behavior is enough that as many as 47 female students (60.3%) of 78 respondents.